2008
DOI: 10.1523/jneurosci.3840-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Induces Changes in Electrophysiological Properties and Ion Channel Expression of Reticulospinal Neurons in Larval Lamprey

Abstract: In larval lamprey, hemitransections were performed on the right side of the rostral spinal cord to axotomize ipsilateral reticulospinal (RS) neurons. First, at short recovery times (2-3 weeks), uninjured RS neurons contralateral to hemitransections fired a smooth train of action potentials in response to sustained depolarization, whereas axotomized neurons fired a single short burst or short repetitive bursts. For uninjured RS neurons, the afterpotentials of action potentials had three components: fast afterhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(89 citation statements)
references
References 58 publications
5
82
2
Order By: Relevance
“…Several in vitro and in vivo studies have shown that electrical stimulation plays an important role in neurite extension and the regeneration of transected nerve ends [95][96][97]. We have shown as the combination of a non-invasive, wireless stimulation with US in the presence of piezoelectric nanoparticles incubated with cells, is able to elicit the same phenomena derived from a "classical" electric stimulation, i.e., a markedly pronounced outgrowth of neuronal processes in PC12 cultures.…”
Section: Effects Of Indirect Stimulation Of Piezoelectric Nanoparticlesmentioning
confidence: 52%
“…Several in vitro and in vivo studies have shown that electrical stimulation plays an important role in neurite extension and the regeneration of transected nerve ends [95][96][97]. We have shown as the combination of a non-invasive, wireless stimulation with US in the presence of piezoelectric nanoparticles incubated with cells, is able to elicit the same phenomena derived from a "classical" electric stimulation, i.e., a markedly pronounced outgrowth of neuronal processes in PC12 cultures.…”
Section: Effects Of Indirect Stimulation Of Piezoelectric Nanoparticlesmentioning
confidence: 52%
“…However, a recent work on lamprey neurones [38] indicates that an increase in calcium current through L-type calcium channels results in an inhibition of neurite outgrowth. The same increase in calcium current is seen in a CS4 enriched environment, as our data suggest (Figure 4), and thus it is not possible to completely rule out the possibility that CSs could also act on axonal regeneration via a surface screening effect.…”
Section: Discussionmentioning
confidence: 98%
“…For example, under an applied potential difference, osteoblast-like cells migrate toward negative electrodes, whereas osteoclasts migrate toward positive electrodes. 70 Several in vitro and in vivo studies have shown that ES plays a critical role in neurite extension and regeneration of functional nerve connections, 71,72 promoting nerve regeneration in gaps less than 7 mm. 73 ES is also capable of inducing changes in cell shapes and for promoting cell alignment along the direction of ES application.…”
Section: Electric Currentmentioning
confidence: 99%